Towards a semi-automated approach for systematic literature reviews - Denzler, Tim; Enders, Martin; Akello, Patricia (27th Annual Americas Conference on Information Systems, AMCIS 2021, 2021)
Given the growing output of scientific literature, researchers are faced with a daunting challenge when it comes to performing systematic literature reviews. Hence, the use of Information Systems to achieve operational excellence has gained increasing importance in systematic literature reviews. However, existing solutions to support systematic literature reviews are often restrained to a single aspect of the process or lack interoperability. As such, researchers may not be able to efficiently leverage recent promising advancements in Machine Learning and Text Analytics. Therefore, we developed a flexible and modifiable artifact that aims to support systematic literature review processes from a holistic point of view. We expect our artifact to be a first step towards semi-automation of systematic literature reviews, which will gain relevance in the near future, as the trend of rising scientific literature output is expected to continue. Our development process follows a Design Science Research approach including continuous evaluation.
CRIS-Team WoS Importer:2021-08-20
Keywords: Automation; Design science; Information systems; Literature review; Machine learning; Text analytics